Distribution process, challenges and ways to overcome such challenges for domestic category of Laugfs Gas Bangladesh Ltd - Hossain, Tanvir (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.